A new replacement name for Chlorostoma lischkei Pilsbry, 1889 (not of Tapparone-Canefri, 1874) (Vetigastropoda: Trochida: Tegulidae). (1st October 2020) - Yamazaki, Daishi; Hirano, Takahiro; Chiba, Satoshi; Fukuda, Hiroshi
ABSTRACT: Tegula xanthostigma (A. Adams, 1853) has two shell colour forms: a black form and a brown-green form that was once named as Chlorostoma lischkei Pilsbry, 1889. Recent molecular phylogenetic and ecological studies have demonstrated that these two forms are genetically distinct and furthermore differ in habitat usage patterns. It is thus reasonable to separate them as two different species. The black shell form corresponds to T. xanthostigma, but the name C. lischkei for the brown-green shell form is a junior primary homonym of C. lischkei Tapparone-Canefri, 1874 and thus invalid. We here propose the new replacement name T. kusairo nom. nov. for C. lischkei Pilsbry, 1889.